Different suturing techniques in thoracic incision: protocol for a feasibility randomised controlled trial. Issue 1 (15th January 2019) - Liu, Zonghui; Liu, Xiangyu; He, Lin; Yu, Xueyuan; Wang, Lu; Wang, Rui; He, Youcheng; Hao, Xiaoyan; Tang, Zhishui; Su, Yingjun; Shu, Maoguo
Abstract : Introduction: Based on the principles of the ideal skin closure technique, we previously described a suture technique (wedge-shaped excision and modified buried vertical mattress suture (WE-MBVMS)) that could provide excellent outcomes for the most demanding surfaces. However, adequate clinical comparative evidence supporting improved outcomes is lacking. Thus, the purpose of this protocol is to establish the feasibility of conducting a fully randomised controlled trial (RCT) comparing the clinical effectiveness of WE-MBVMS with a buried intradermal suture (BIS) in closing thoracic incision. Methods and analysis: This study is a feasibility RCT of WE-MBVMS and BIS in patients undergoing surgery for costal cartilage harvesting. Seventy-eight participants are expected to participate in the study and will be randomised in a ratio of 1:1 to WE-MBVMS or BIS. Trial feasibility will be assessed by the number of participants assessed for eligibility, recruitment rates, reasons for ineligibility or non-participation, time for interventions, withdrawal and retention at all follow-up points (3, 6 and 12 months), follow-up rates and reasons for withdrawing from the trial. In addition, clinical data regarding the cosmetic results of scars will be collected to inform the sample size for a fully powered RCT. Ethics and dissemination: This study has been approved by The First Affiliated Hospital of Xi'an Jiaotong University Institutional Review Board (XJTU1AF2017LSK-120). The findings will be published in peer-reviewed journals. Trial registration number: ChiCTR-INR-17013335; Pre-results.